Environmental niche overlap between common and dusky dolphins in North Patagonia, Argentina - Svendsen, Guillermo (2015)
Research on the ecology of sympatric dolphins has increased worldwide in recent decades. However, many dolphin associations such as that between common dolphins (Delphinus delphis) and dusky dolphins (Lagenorhynchus obscurus) are poorly understood. The present study was conducted in the San Matías Gulf (SMG) ecosystem (North Patagonia, Argentina) where a high diet overlap among both species was found. The main objective of the present work was to explore the niche overlap of common and dusky dolphins in the habitat and temporal dimensions. The specific aims were (a) to evaluate the habitat use strategies of both species through a comparison of their group attributes (social composition, size and activity), and (b) to evaluate their habitat preferences and habitat overlap through Environmental Niche modeling considering two oceanographic seasons. To accomplish these aims, we used a historic database of opportunistic and systematic records collected from 1983 to 2011. Common and dusky dolphins exhibited similar patterns of group size (from less than 10 to more than 100 individuals), activity (both species use the area to feed, nurse, and copulate), and composition (adults, juveniles, and mothers with calves were observed for both species). Also, both species were observed travelling and feeding in mixed-species groups. Specific overlap indices were higher for common dolphins than for dusky dolphins, but all indices were low, suggesting that they are mainly segregated in the habitat dimension. In the case of common dolphins, the best habitats were located in the northwest of the gulf far from the coast. In the warm season they prefer areas with temperate sea surface and in the cold season they prefer areas with relatively high variability of sea surface temperature. Meanwhile, dusky dolphins prefer areas with steep slopes close to the coast in the southwestern sector of the gulf in both seasons.